Process Simulation of Ammonia as a Hydrogen Carrier for Storage and Transportation - GHOUIREG Salah; BENABDALLAH Abdelkarim; BENSENOUCI Ahmed (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT : GENIE MECANIQUE, 2025)
This thesis presents a simulation study of ammonia synthesis and decomposition using Aspen Plus. The work evaluates process conditions, energy requirements, and yields to provide insights into the feasibility and efficiency of ammonia as a hydrogen carrier. The results highlight ammonia’s dual role as both an industrial product and an enabler for hydrogen storage and transport, emphasizing its importance in future sustainable energy systems. By integrating process modeling with energy transition needs, the study demonstrates the potential of ammonia to support the development of a reliable hydrogen economy.
Option: Renewable Energy